Prevalencia de ancilostomiasis canina en la ciudad de Machala - Apolo Naranjo, Bélgica Marlene (2007)
The present investigation has more than enough canine Ancilostomiasis was carried out in the different parishes of the you take care of Machala, county of El Oro, during the months of September to November of the 2007, with the following objectives: 1. to determine the prevalencia of Ancilostomiasis according to the age and the hábitat.; 2. to Establish the infection degree parasitaria. El number of investigated animals was of 250 distributed in the six urban parishes of the you take care. For the taking of sample was used extractors of grounds that were placed in boxes of plastics and labeled respectively. The method that was used for the contaje of eggs was the technique of McMaster. The prevalencia of canine Ancilostomiasis in the you take care it was of 23,6 %, in the urban parish Nueve de Mayo that presented a bigger percentage and 15,2 % corresponded to the sharp infection. The biggest prevalencia in the illness was presented in puppies and in dogs that its hábitat was the patio.